Comparison of blade optimisation strategies for the IEA 15MW reference turbine - Scott, Samuel; Greaves, Peter; Macquart, Terence; Pirrera, Alberto (Journal of physics. Conference series, 2022)
Reference wind turbine models are crucial for enabling the research community to advance technology and meet the challenges associated with upscaling. The IEA 15 MW is one such reference model, designed using NREL’s WISDEM tool, which enables researchers to perform system-level analysis and optimisation. However, the authors have found the blade to be structurally infeasible when subject to aero-servo-elastic simulations and finite-element (FE) analyses. Given the shortcomings, this work aims to develop an updated blade model for the 15 MW turbine platform using the design tool A eroelastic T urbine O ptimisation M ethods (ATOM). Two optimisation processes, with a comprehensive suite of feasibility constraints, are applied: 1) a frozen-loads mass minimisation with fixed planform, and 2) an aero-servo-structural levelised cost of energy (LCoE) minimisation. Results show the frozen-loads optimised design results in a 0.93% increase in LCoE due to the mass penalty of attaining feasibility. In contrast, the aero-structural optimised design results in a 2.29% reduction in LCoE due to mass reductions and increased energy capture—highlighting the benefits of an integrated design process. FE shell analysis of the optimised blades indicates the strength predictions in ATOM are accurate and the main load-bearing spar caps are optimally utilised. Whilst an improvement on the baseline, buckling load factors do not satisfy the target values, indicating the lower fidelity checks in ATOM are non-conservative. The WindIO yaml files for these optimised designs are freely available online.